On the Stability of the Maximum Term of the Entire Dirichlet Series - Skaskiv, O. B.; Trakalo, O. M. (Ukrains’kyi Matematychnyi Zhurnal, 2005)
We establish necessary and sufficient conditions for logarithms of the maximal terms of the entire Dirichlet series $F(z) = \sum^{+∞}_{n=0}a_n e^{zλ_n}$ and $A(z) = \sum^{+∞}_{n=0}a_n b_n e^{zλ_n}$ to be asymptotically equivalent as ${\rm Re}\;z → +∞$ outside some set of finite measure.